Estudo das componentes do balanço de energia em uma cultura de arroz irrigado no Sul do Brasil - Sena, Julio Cesar Lopes (2012)
This dissertation presents a study on the experimental site of Cachoeira do Sul-RS, Brazil. The objective of this study was to estimate the components of the Energy Balance Closure on the surface of a rice paddy field. The research was divided into three periods: I-dry soil, not irrigated and low vegetation, remaining from the last rice harvest, II - irrigated soil in which the area was being prepared for planting pre-germinated rice, and period III - irrigated soil already planted with rice and at reproductive phase. Also, we performed measurements of leaf area index, rice height and monitoring of the water level on the field. Temperature measurements at the water level on the crop were used to estimate the energy flow through this order to improve the EBC. For data acquisition, were used temperature sensors in the soil, heat flux plate, net radiation sensor, wind speed and direction and infrared open path gas analyzer. The results showed that the sum of the components Energy Balance Closure are not equivalent to the available energy in the surface, and the surface energy imbalance is influenced by the surface coverage.